Skip to main content
Solve for x
Tick mark Image
Graph

Similar Problems from Web Search

Share

1-3x^{2}=0
Divide both sides by 2. Zero divided by any non-zero number gives zero.
-3x^{2}=-1
Subtract 1 from both sides. Anything subtracted from zero gives its negation.
x^{2}=\frac{-1}{-3}
Divide both sides by -3.
x^{2}=\frac{1}{3}
Fraction \frac{-1}{-3} can be simplified to \frac{1}{3} by removing the negative sign from both the numerator and the denominator.
x=\frac{\sqrt{3}}{3} x=-\frac{\sqrt{3}}{3}
Take the square root of both sides of the equation.
1-3x^{2}=0
Divide both sides by 2. Zero divided by any non-zero number gives zero.
-3x^{2}+1=0
Quadratic equations like this one, with an x^{2} term but no x term, can still be solved using the quadratic formula, \frac{-b±\sqrt{b^{2}-4ac}}{2a}, once they are put in standard form: ax^{2}+bx+c=0.
x=\frac{0±\sqrt{0^{2}-4\left(-3\right)}}{2\left(-3\right)}
This equation is in standard form: ax^{2}+bx+c=0. Substitute -3 for a, 0 for b, and 1 for c in the quadratic formula, \frac{-b±\sqrt{b^{2}-4ac}}{2a}.
x=\frac{0±\sqrt{-4\left(-3\right)}}{2\left(-3\right)}
Square 0.
x=\frac{0±\sqrt{12}}{2\left(-3\right)}
Multiply -4 times -3.
x=\frac{0±2\sqrt{3}}{2\left(-3\right)}
Take the square root of 12.
x=\frac{0±2\sqrt{3}}{-6}
Multiply 2 times -3.
x=-\frac{\sqrt{3}}{3}
Now solve the equation x=\frac{0±2\sqrt{3}}{-6} when ± is plus.
x=\frac{\sqrt{3}}{3}
Now solve the equation x=\frac{0±2\sqrt{3}}{-6} when ± is minus.
x=-\frac{\sqrt{3}}{3} x=\frac{\sqrt{3}}{3}
The equation is now solved.